Factors Determining the Behavioral Intention of Using Food Delivery Apps during COVID-19 Pandemics - Muangmee, Chaiyawit; Kot, Sebastian; Meekaewkunchorn, Nusanee; Kassakorn, Nuttapon; Khalid, Bilal (Journal of theoretical and applied electronic commerce research, 2021)
The purpose of this study was to investigate the factors determining the behavioral intention of using food delivery apps (FDAs) during COVID-19 pandemics, under a case study of Bangkok, Thailand. The study was necessitated by the increased use of FDAs during the lockdown; online transactions were considered important in preventing the spread of the virus. The study used quantitative techniques involving structural equation model (SEM) to evaluate the effects of exogenous variables on endogenous variables. Primary data were collected from people who had installed and used FDAs. The findings indicated that performance expectancy, effort expectancy, social influence, timeliness, task technology fit, perceived trust, and perceived safety significantly influence the behavioral intention to use (BIU) to use food delivery apps during the COVID-19 pandemic. To this end, effort should be intensified to study and understand FDAs as it pertains to safety and usage.